GABRA6 and SLC6A4 genotypes are correlated with the fasting blood glucose and physical fitness in the seemingly healthy young adults - Viskasari P Kalanjati; Mariana Wahjudi; Kusuma E. Purwantari; Visuddho; Peppy Nawangsasi; Rury T. Oktariza; Krisnawan A. Pradana; Dzanuar Rahmawan; Bambang E. Suwito (Universitas Airlangga, 2023)
Introduction: We examined environmental and genetic factors potentially correlated with the blood glucose and physical fitness in Kediri, East Java, Indonesia to elucidate the predominant cardiovascular disease risk. Methods: This was a cross-sectional study on 68 adults aged 18-22 years. Direct interview was conducted to get socio-economy, daily diets (rice/ R, snacks and sweets/ SS, veggies and fruits/ VF), daily activity (locomotors and non-locomotors) data. Peripheral blood-GABRA6 and SLC6A4 polymorphisms, fasting blood glucose (FBG), blood pressure, 3 fitness parameters (1 min push-up, 3 minutes step up, pulse rate after 3 minutes step-up) were measured by 2 independent and pre-trained medical doctors. Kruskal-Wallis, Chi-Square, and eta-coefficient tests were used to seek differences between genotypes and correlation strength between variables, respectively (significant if p<0.05). Results: Both gene's genotypes showed significant correlations with the FBG (p=0.042, p=0.013, respectively); GABRA6 polymorphism significantly correlated with SU (p=0.033). There was a significant difference in the FBG between 2 VF subgroups (p=0.02). Strongest association was found between FBG and SLC6A4 (Î·=0.3); PR and GABRA6 (Î·=0.168), PU and SLC6A4 (Î·=0.38); SU and Locomotors (Î·=0.237). Conclusions: In these seemingly healthy young adults, daily diets and the genotypes of both genes have a good association with the FBG and physical fitness levels.